DAUPHINE: a randomized phase II study of danoprevir/ritonavir plus peginterferon alpha‐2a/ribavirin in HCV genotypes 1 or 4. (12th February 2014) - Everson, Gregory; Cooper, Curtis; Hézode, Christophe; Shiffman, Mitchell L.; Yoshida, Eric; Beltran‐Jaramillo, Teresita; Andreone, Pietro; Bruno, Savino; Ferenci, Peter; Zeuzem, Stefan; Brunda, Michael; Le Pogam, Sophie; et al.
Abstract Background & Aims Danoprevir is a hepatitis C virus (HCV) protease inhibitor with activity against genotypes (G)1/G4, which is maintained at lower doses by ritonavir‐boosting. We report results of a large, randomized, active‐controlled phase IIb study of ritonavir‐boosted danoprevir (danoprevir/r) plus peginterferon alpha‐2a/ribavirin (P/R) in treatment‐naive patients with HCV G1/4 infection. Methods Treatment‐naive patients with HCV G1/4 infection were randomized to twice‐daily danoprevir/r 200/100 mg (A, n = 92); 100/100 mg (B, n = 93); or 50/100 mg (C, n = 94) plus P/R for 24 weeks; twice‐daily danoprevir/r 100/100 mg (D, n = 94) plus P/R for 12 or 24 weeks; or P/R alone (E, n = 44) for 48 weeks. Patients in the response‐guided therapy arm (D) with an extended rapid virological response (eRVR2: HCV RNA <15 IU/ml during Weeks 2–10) stopped all therapy at Week 12; non‐eRVR2 patients continued all treatment to Week 24. The primary efficacy endpoint was sustained the virological response (SVR24: HCV RNA <15 IU/ml after 24 weeks of untreated follow‐up). Results SVR24 rates in Arms A, B, C, D and E were 89.1%, 78.5%, 66.0%, 69.1% and 36.4%, respectively, in the overall population; 83.6%, 69.6%, 60.3%, 59.2% and 38.5% in G1a‐infected patients, 96.6%, 93.1%, 73.1%, 78.4% and 28.6% in G1b‐infected patients and 100%, 87.5%, 100%, 100% and 66.7% in G4‐infected patients. Danoprevir/r plus P/R was generally well tolerated compared with P/R alone. There was a higher incidence of serious adverse events in danoprevir‐treatment arms, but most were associated with P/R. Conclusions The combination of danoprevir/r plus P/R is efficacious in treatment‐naïve patients with HCV genotype 1 or 4 infection.